2011
DOI: 10.1126/scitranslmed.3002842
|View full text |Cite
|
Sign up to set email alerts
|

T Cells with Chimeric Antigen Receptors Have Potent Antitumor Effects and Can Establish Memory in Patients with Advanced Leukemia

Abstract: Tumor immunotherapy with T lymphocytes, which can recognize and destroy malignant cells, has been limited by the ability to isolate and expand T cells restricted to tumor-associated antigens. Chimeric antigen receptors (CARs) composed of antibody binding domains connected to domains that activate T cells could overcome tolerance by allowing T cells to respond to cell surface antigens; however, to date, lymphocytes engineered to express CARs have demonstrated minimal in vivo expansion and antitumor effects in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
1,926
7
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,109 publications
(1,984 citation statements)
references
References 42 publications
32
1,926
7
19
Order By: Relevance
“…The clinical benefits of this approach have been validated using CAR-CD19 T cells to treat a range of CD19 + hematological malignancies including B cell chronic lymphocytic leukemia (B-CLL) and acute lymphoblastic leukemia (ALL). [29][30][31][32] For example, Grupp and colleagues 30 recently reported a complete remission rate of 92% in pediatric patients with relapsed/refractory CD19 + ALL, while Davila et al 3 achieved an overall complete remission rate of 88% in adults with B-ALL. In many cases, clinical benefit correlated with the ability of infused cells to expand and persist in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical benefits of this approach have been validated using CAR-CD19 T cells to treat a range of CD19 + hematological malignancies including B cell chronic lymphocytic leukemia (B-CLL) and acute lymphoblastic leukemia (ALL). [29][30][31][32] For example, Grupp and colleagues 30 recently reported a complete remission rate of 92% in pediatric patients with relapsed/refractory CD19 + ALL, while Davila et al 3 achieved an overall complete remission rate of 88% in adults with B-ALL. In many cases, clinical benefit correlated with the ability of infused cells to expand and persist in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric antigen receptor (CAR)-redirected T cells have seen success in CD19 + hematological malignancies, leading to cure of acute lymphoid leukemia (ALL) and lymphoma of B-cell origin (1)(2)(3)(4)(5). The success of T-cell based CAR strategies depends on distinct T-cell subsets (6).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators at the University of Pennsylvania reported three patients with advanced CLL who received T-cells modified with a second-generation lentiviral vector 4-1BB-CD19-CAR after receiving lymphodepletion. (Kalos et al 2011) Impressive expansion and anti-tumour activity were seen, with two CRs and one prolonged PR. However, adverse effects, including cytokine release syndrome (CRS) and B cell aplasia with hypogammaglobulinemia, were also observed (see the section on Safety below).…”
Section: Chimeric Antigen Receptor-modified T-cellsmentioning
confidence: 98%